2020
DOI: 10.1002/ente.202000444
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Performance of Solid‐State Lithium Battery Based on Hybridizing Micron‐Sized LATP in a PEO/PVDF‐HFP Heterogeneous Polymer Matrix

Abstract: Solid‐state poly(ethylene oxide) (PEO) electrolyte exhibits a low ionic conductivity at ambient conditions, and large interfacial resistance between PEO and electrodes obstructs its applications in lithium metal batteries. Heterogeneous solid electrolytes (HSEs) are an alluring solution for the exploitation of PEO. Herein, PEO/poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP)/micron‐sized Li1.4Al0.4Ti1.6(PO4)3 (LATP) heterogeneous solid electrolytes are originally prepared to decrease the crystallini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…So far, CSEs with sufficiently high ionic conductivity at the ambient temperature for applications in solid-state lithium batteries can hardly be achieved by simply mixing the polymer and inorganic SSEs . Recently, a CSE with a low ionic conductivity of only 0.03 mS cm –1 at 30 °C was reported, which was obtained by introducing poly­(vinylidene fluoride- co -hexafluoropropylene) (PVDF-HFP)/micrometer-sized Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 into the PEO matrix . However, it has been demonstrated that the interfaces between the inorganic fillers and polymer matrix can play a dominating role in Li-ion conduction, and CSEs with sufficiently high ion conductivity at room temperature can be achieved by delicately designing the interfaces between the inorganic fillers and polymer matrix. , In a previous study, contaminants on the surface of the garnet fillers were utilized as reaction initiators to generate Li-conducting ether oligomers at the interfaces between fillers and polymer matrix, resulting in greatly improved ion conductivity of CSEs.…”
Section: Introductionmentioning
confidence: 99%
“…So far, CSEs with sufficiently high ionic conductivity at the ambient temperature for applications in solid-state lithium batteries can hardly be achieved by simply mixing the polymer and inorganic SSEs . Recently, a CSE with a low ionic conductivity of only 0.03 mS cm –1 at 30 °C was reported, which was obtained by introducing poly­(vinylidene fluoride- co -hexafluoropropylene) (PVDF-HFP)/micrometer-sized Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 into the PEO matrix . However, it has been demonstrated that the interfaces between the inorganic fillers and polymer matrix can play a dominating role in Li-ion conduction, and CSEs with sufficiently high ion conductivity at room temperature can be achieved by delicately designing the interfaces between the inorganic fillers and polymer matrix. , In a previous study, contaminants on the surface of the garnet fillers were utilized as reaction initiators to generate Li-conducting ether oligomers at the interfaces between fillers and polymer matrix, resulting in greatly improved ion conductivity of CSEs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] In fact, linear poly (ethylene oxide) (PEO)‐based state polymer electrolyte (SPE) is the most representative one. [ 5–8 ] However, the linear PEO electrolyte shows extremely low ionic conductivity at room temperature (RT, 10 −7 –10 −6 S cm −1 ). [ 9 ] Even worse, poor mechanical property and inferior interface compatibility with electrodes further hold back its practical use in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Xue and co-workers hybridized micrometer-sized LATP with a PEO/PVDF-HFP heterogeneous polymer matrix. The as-prepared CSE shows an ionic conductivity of 3.01 × 10 –5 S cm –1 , a Li + transfer number of 0.55, and a broad electrochemical stable window of 5.31 V at 30 °C . In addition, a fluoroethylene carbonate (FEC) additive was also used to optimize the performance of a PEO-LATP CSE with an enhanced conductivity of 1.99 × 10 –4 S cm –1 at 30 °C .…”
Section: Introductionmentioning
confidence: 99%